Real‐time three‐dimensional (3D) echocardiographic characterisation of an atrial septal defect in a horse. Issue 4 (6th July 2020) - Redpath, Adam; Marr, Celia M; Bullard, Caroline; Hallowell, Gayle D
Abstract: Atrial septal defects have been well reported in humans and dogs and the principles of intervention have been well established. In contrast, there is very little information published about these congenital anomalies in horses. True ASDs are regarded as rare and little is known about the clinical significance of these defects in horses. An 11‐year‐old Thoroughbred gelding with a history of poor performance was diagnosed with an atrial septal defect, measuring approximately 2 cm in diameter, on 2D transthoracic echocardiography. Real‐time three‐dimensional (3D) echocardiography was used to map the structure of the defect and was useful in fully characterising the ASD in this case. Abstract : Atrial septal defects (ASDs) are uncommon findings in the horse and are usually asymptomatic. This report documents an unusually large ASD that was characterised using real‐time 3D echocardiography.